Pengambilan keputusan investasi investor di pasar modal Indonesia ditinjau dari Teori Reasoned Action - Indra Listyarti (Journal of Business & Banking, 2017)
The objective of this research is to examine the factors that influence the investor beha-vior when making investment decisions in terms of Reasoned Action Theory. This re-search consists of 190 investors in the Indonesian capital market and the data were ana-lyzed by using multiple linear regression. The results show that Macro factors have posi-tive significantly effect on Technical Information. Financial Information, Macro Factors and Subjective Norm has positive significantly effect on investor intentions. Investors' intentions and Financial Information have positive significantly effect on Investment Decisions. Furthermore the results also found that financial information has dominant contribution in detemining investor intentions and investment decisions.